The Agrarian Historiography of Chile: Foundational Interpretations, Conventional Reiterations, and Critical Revisionism - Robles-Ortiz, C (UNIV MURCIA, 2020)
This article examines the development of Chilean agrarian historiography in the last four decades, by means of an introductory overview organized as a chronological reconstruction. It selectively focuses on relevant authors and works, the problems and questions they addressed, their main arguments and contributions, as well as their flaws and limitations. In doing so, the article constructs debates that never took place, because development of this field has been limited by the scarcity of specialized works, the different contexts in which they were produced, and the lack of institutional spaces for systematic debate.Agrarian historiography has only recently become a distinctive discipline in Chile and is therefore an incipient field. In the last fifteen years, a new revisionist agrarian historiography has begun to revitalize the study of Chilean rural history through critical dialogue with foundational interpretations from the 1970s, leaving behind the conventional reiterations of the 1980s.